Covid-19’s impact on radiotherapy in the Republic of Srpska - Kolarević, Goran; Jaroš, Dražan; Pavičar, Bojan; Marošević, Goran (Vojnosanitetski pregled, 2022)
Background/Aim. Coronavirus disease 2019 (COVID-19) significantly affects patients with any type of chronic disease, especially the ones with neoplasm. The aim of this study was to investigate the impact of the COVID-19 pandemic on the weekly number of external beam (EB) radiotherapy (RT) (EBRT) fractions and monthly brachytherapy (BT) applications without intentional hypofractionation. We also investigated how the pandemic affected the number of EBRT patients younger or older than 70 years. Methods. The Affidea Radiotherapy Center, Banja Luka (BL RT Center), provides RT to the population (1.15 million) of the Republic of Srpska (Bosnia and Herzegovina). We analyzed the period of 14 months before the onset and the same period during COVID-19. Results. The average weekly number of EBRT fractions from January 2019 to the end of February 2020 was 680.5 [standard deviation (SD) 67.4], and from March 2020 to the end of April 2021, it was 617.1 (SD 96.4). During April 2020, the weekly number of the EBRT decreased by 67.9% compared to the same period in 2019, while in March 2021, it fell by 42.4%. Paired samples t-test showed that the occurrence of the COVID-19 pandemic had a statistically significant effect [t(60) = 4.627, p < 0.05] on the reduction in the number of weekly EBRT fractions in the BL RT Center. When comparing number of EBRT patients over 70 years old to those fewer than 70 years old, the decrease was 16.3% vs. 1.6%, respectively. The Wilcoxon signed-rank test revealed that the COVID-19 pandemic had a statistically significant effect (Z = -2.42, p = 0.016) on reducing the number of monthly BT applications. Conclusion. A statistically significant decline in EBRT and BT was observed in BL RT Center for the first fourteen months of the pandemic. The "waves" of the pandemic "closed" the medical wards needed for the diagnosis and therapy of oncology patients and converted them into COVID-19 wards. Therefore, some oncology patients who would have had an indication for RT never received it.